Influence of Customer Experience on Customer Loyalty with Competitive Advantage as a Media Variable on Learnstuff Center - Olivia Agatha; Metta Padmalia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine how customer experience affects customer loyalty at Learnstuff.Center, using competitive advantage as a mediating variable. The study involved respondents selected through a census methodology and employed a quantitative approach with a survey method. The findings indicated that customer experience has a significant and positive impact on both competitive advantage and customer loyalty. Furthermore, competitive advantage was also found to significantly and positively influence customer loyalty. It was also demonstrated that competitive advantage mediates the relationship between customer experience and customer loyalty. These findings highlight the importance of Learnstuff.Center to focus on enhancing customer experience as a strategy to build a competitive advantage and strengthen customer loyalty in the online education industry.